An Illustrated Dictionary of Ceramics - Savage, George and Newman, Harold (London Thames and Hudson, 1974)
A reference for collectors, dealers and all those interested in ceramics, embracing the vast range of ceramic types and terminology, from antiquity to the present day. It is also concerned with the physical nature of pottery and porcelain, as with periods, dynasties and general categories of wares.
Includes Illustrations and index.
Keywords: Ceramics -- Dictionaries